Question Mark Ear Deformity : A Combined Method for Correction (2011)
ABSTRACT: Question mark ear deformity or Cosman ear is a very uncommon congenital alteration. The deformity includes a cleft between the posterior helix and the lobule, an increase in anterior projection, an abnormal superior third that modifies the superior crura and the scaphoid fossa, partial or complete absence of the antihelix, transposition of the lobule and antihelix (severe cases), and postauricular tags. The authors present a case of moderate question mark ear deformity treated using Mustarde sutures and two cartilage grafts to correct the support and the contour defect. Adequate correction of the deformity and symmetry was achieved for both ears. The technique described in this report is suitable for minimal to moderate defects.